Customer satisfaction and influencing mechanism for fully decorated residential building based on SEM method under the “dual-carbon” goal: evidence from Wuhan, China - Qinyan Dai; Weiwei Zuo; Shuqiang Wang; Ning Yan (Journal of Asian Architecture and Building Engineering)
While fully decorated residential buildings offer environmental benefits aligned with “dual-carbon” goal, its ecological potential remains constrained by low customer satisfaction and frequent renovations. To determine the decisive factors affecting customer satisfaction and quantify their interaction mechanisms in China’s fully decorated residential building sector, this study develops a second-order SEM incorporating six latent variables: perceived quality (PQ), perceived service (PS), perceived value (PV), corporate image (CI), customer expectation (CE), and customer satisfaction (CS). PQ is innovatively operationalized through four dimensions: construction quality (CQ), material and equipment quality (MEQ), design quality (DQ), and personalized needs (PN), while PS is decomposed into maintenance service (MS) and property management service (PMS). Analysis of 360 valid questionnaires from Wuhan reveals that CE, CI, PQ, PS, and PV exert significant positive impacts on CS, with PQ and PS demonstrating the strongest effects. This study identifies three key pathways to enhance customer satisfaction in fully decorated residential buildings: upgrading material and equipment standards, improving construction standards, and optimizing after-sales services to strengthen corporate image. The findings enrich the theoretical discourse on fully decorated residential building satisfaction, provide novel analytical perspectives, and offer empirically validated strategies for policymakers and developers to improve housing governance and promote green, sustainable industry development.